Polish and German press reports on cooperation between the foreign ministers of both countries in resolving the conflict in Ukraine (February-June 2014) - Patecka-Frauenfelder, Anna (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
Polish-German relations in the first half of 2014 were dominated by the Ukraine crisis. This study is an attempt to answer the question of how Polish and German press assessed the cooperation of both countries in resolving the conflict in Ukraine; to what extent the most widely read magazines associated themselves with the decisions of their politicians and the feelings of their own societies and how much understanding they showed for the arguments of their EU partner. The analysis focuses on the unprecedented mission of the Weimar Triangle foreign ministers to Ukraine in February 2014, which led to an agreement between the Ukrainian opposition and President Viktor Yanukovych. A turning point was the visit paid by Radoslaw Sikorski and Frank-Walter Steinmeier to St. Petersburg in June 2014. The next meetings agreed on by EU partners were held without inviting the Polish partner. In view of the speed of events in the selected time interval, the articles subjected to analysis were taken from the most widely read online editions of national daily newspapers in Poland and Germany.